Teaching Arabic as a Foreign Language in Multicultural Classrooms: A Comparative Study - Mansouri Al-Ahmady; Fatma Hunaini (IJAS: International Journal of Arabic Studies, 2025)
The teaching of Arabic as a foreign language (TAFL) in multicultural classrooms presents both opportunities and challenges. Learners from different linguistic and cultural backgrounds bring diverse expectations, which influence motivation, classroom interaction, and learning outcomes. This study explores the comparative effectiveness of teaching strategies in multicultural settings by focusing on how teachers adapt to cultural differences while promoting communicative competence.Using a qualitative comparative approach, data were collected through classroom observations, teacher interviews, and student questionnaires. The findings reveal that effective instruction requires culturally responsive pedagogy, flexible teaching methods, and the integration of multilingual resources. Moreover, intercultural dialogue plays a vital role in overcoming barriers to pronunciation, comprehension, and vocabulary retention.The study concludes that adopting inclusive pedagogical practices enhances not only Arabic language acquisition but also intercultural understanding, offering important implications for teacher training and curriculum development